2018
DOI: 10.1177/1524839918762123
|View full text |Cite
|
Sign up to set email alerts
|

A Participatory Process to Engage Appalachian Youth in Reducing Sugar-Sweetened Beverage Consumption

Abstract: Children and adolescents consume excessive amounts of sugar-sweetened beverages (SSBs), which are associated with adverse health outcomes. We describe a yearlong participatory research study to reduce SSBs in Central Appalachia, where excessive consumption is particularly prevalent. This study was conducted in partnership with a community advisory board in Southwest Virginia. Nine "youth ambassadors," aged 10 to 13 years helped to systematically adapt SIPsmartER, an effective theory-based program for Appalachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…Youth are traditionally excluded or overlooked from social action or research engagement, and a limited number of published studies have been youth-led [17,18]. We could identify only three published participatory research studies that involved youth in Appalachia; these studies focused on obesity/diabetes [7] and sugar-sweetened beverage consumption [8,9]. However, this project may be the first to equip youth in Appalachia with sufficient agency to guide the intervention development and formative assessment for an environmental health focus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Youth are traditionally excluded or overlooked from social action or research engagement, and a limited number of published studies have been youth-led [17,18]. We could identify only three published participatory research studies that involved youth in Appalachia; these studies focused on obesity/diabetes [7] and sugar-sweetened beverage consumption [8,9]. However, this project may be the first to equip youth in Appalachia with sufficient agency to guide the intervention development and formative assessment for an environmental health focus.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas photovoice has been used in previous studies with Appalachian youth [7,8,9], to our knowledge, this study is the first to use the approach to address environmental health. This paper provides findings from an exploratory study in which youth identified factors that they perceived as important environmental determinants of respiratory illness in their community.…”
Section: Introductionmentioning
confidence: 99%
“…Human agents may play an important role in both drinking and quitting SSB consumption [c.f., (63)]. In line with Franken et al (64), participants mentioned the role of their social network, in particular friends and social media influencers (65). It may also be recommendable to involve parents and school in the process, since infants have a natural strong preference for sweet taste and it has been observed that early introduction of added sugars in the diet may promote sweet taste preference (66)(67)(68).…”
Section: Discussionmentioning
confidence: 77%
“…Analysing information Allen et al, 2008 Application of information Hearne, 2008 Critical thinking skills Lane et al, 2019;Roberts & Kreeger, 2019;Young & Goodman, 2015 Dissemination of information Nagro et al, 2018 Evaluation of information Hagan & Donavan, 2013;Keselman et al, 2019;Smith & Boster, 2009;Vessey & Miola, 1997. Information engagement Hagan et al, 2018 Information gathering Hawley et al, 2016 Information management Hagan & Donovan, 2013 Information seeking skills Hagan & Donovan, 2013;Kratzke et al, 2018 Information sharing Bloodgood & Clough, 2017;Scharff et al, 2018;White et al, 2010 Interpreting information Lane et al, 2019 Knowledge transfer Abram, 2017 Media literacy De Castro & Levesque, 2018…”
Section: Il Skillmentioning
confidence: 99%